2017
DOI: 10.5455/ajvs.249419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Water Treatment and Some Additives on Growth Performance, Some Blood Biochemical Parameters and Intestinal Health of Growing Pekin Ducklings

Abstract: Key words:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
(32 reference statements)
2
7
2
Order By: Relevance
“…These data are probably the main reason for improvements in the absorption of intestinal nutrients and increased enteric functions. These results were consistent with the results reported by El-Katcha et al [56], who showed increases in the length of intestinal villi, thus indicating improved nutrient absorption and increased body weights of growing Pekin ducklings compared with those of the control group. Saleh et al [62] also observed significant enhancements of the pancreas in diabetic pancreatic rats treated with magnetic water, which exhibited a final size and cellular structures of islets of Langerhans that were nearly comparable to those of the control group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These data are probably the main reason for improvements in the absorption of intestinal nutrients and increased enteric functions. These results were consistent with the results reported by El-Katcha et al [56], who showed increases in the length of intestinal villi, thus indicating improved nutrient absorption and increased body weights of growing Pekin ducklings compared with those of the control group. Saleh et al [62] also observed significant enhancements of the pancreas in diabetic pancreatic rats treated with magnetic water, which exhibited a final size and cellular structures of islets of Langerhans that were nearly comparable to those of the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Alhassani and Amin [55] recorded no significant differences in the body weight, WG, mortality rate, feed intake, FCR, performance index, and viability of Cobb-500 broiler chicks treated with magnetic water using a magnetizer of 500 gausses with 5, 10, and 15 min speeds; however, the contradiction might be attributed to the strength of the magnetic field used. El-Katcha et al [56] recorded an improved feed conversion and PI in Pekin ducklings and attributed these improvements to the ability of magnetic water to increase the intestinal villi length, thus improving nutrient absorption and body weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of magnetic field to improve water quality is significant interest due to low cost compared to chemical and physical treatment (Ebrahim and Azab, 2017), also it is an environmentally friendly way (Silva and Dobranszki, 2014). Studies revealed that exposing water to magnetic field influences the water's physiochemical properties which affect the biological properties of the organisms that consume the water (El Katcha et al, 2017;Sedigh et al, 2019& Mahmoud et al, 2019. Magnetic field transfers water from dead to live (Hussein et al, 2015).…”
Section: Intoductionmentioning
confidence: 99%